Tindak Tutur Direktif dan Asertif dalam Cerpen Sleep Deprived Karya Charissa E - Ahmad Fudholi; M Arief Hermawan; Ngatoillah Ngatoillah; Nicky Rosadi (PROPAGANDA, 2023)
This study aims to find out the types of directive and assertive speech acts contained in the short story entitled Sleep Deprived by Charissa E. The data source in this research is the short story Sleep Deprived by Charissa E which was published on the short story site mu.com in March 2021 through a Pragmatic study. Speech Act. The research method uses qualitative methods that can be used to examine the objects studied naturally and as they are. In qualitative research, the task of the researcher is as a key instrument in collecting data which will later be studied and analyzed. The data collection technique used is observation followed by a documentation study. Documentation studies are carried out by analyzing pragmatic speech acts related to Directive, Assertive, Directive, and Commissive aspects. Based on the results of the study, it can be concluded that there are 19 speech acts divided into 9 directive speech acts in the form of questions, 5 directive speech acts in the form of orders, and 5 assertive speech acts in the form of statements in the short story. Hopefully this research can be an alternative reference for other researchers who want to research pragmatic speech acts, especially about directive and assertive speech acts in short stories.